Cyber law in Malaysia: principles and practices - Zulhuda, Sonny; Karim, Ridoan (Sweet & Maxwell, Thomson Reuters Asia Sdn Bhd, 2024)
Cyber law is an ever-evolving field that is becoming increasingly important. This is especially true in today’s world, where almost every aspect of our lives relies on digital technology. The intersection of law, technology, and governance has created a unique set of challenges, making it crucial for individuals to gain expertise in cyber law. In this book, we aim to provide valuable legal and policy insights into Malaysian cyber laws, starting by showcasing the international context and then to assessing Malaysian development from the legislative and judicial perspectives and also the administrative measures taken. Where applicable, references to international treaties and foreign laws and cases are also made and such sources are discussed.